(untitled) (Bangladesh Journal of Medical Microbiology, 2018)
Gout is one of the oldest diseases of the medical history that results from the deposition of monosodium urate crystals in joint structures and in periarticular sites in the form of tophi. The evaluation of synovial fluid is integral for the diagnosis of gout and other arthritis of microcrystals. The objective of this cross-sectional study was to evaluate the analysis of synovial fluid by polarizing and light microscopy using wet film and Diff Quik stained films and evaluating usefulness of Diff Quik stain in identifying monosodium urate (MSU) crystals on permanent mounted slides. It was conducted on 100 clinically suspected gout patients in the Department of Clinical Pathology, Bangabandhu Sheikh Mujib Medical University, Dhaka from May 2008 to April 2009. Polarizing Microscopy detected the presence of MSU crystals in 35.71% cases from wet films and 36.73% cases from Diff Quik stained films. Light Microscopy detected crystals in 28 (28.57%) cases from Diff Quik stained samples and in 31.63% cases from wet film samples. Considering wet film polarizing microscopy as gold standard, the sensitivity and specificity of wet film light microscopy was 88.6% and 100.0% respectively, whereas sensitivity and specificity were 80.0% and 100.0% respectively in Diff Quik light microscopy.In Diff Quik polarizing microscopy, sensitivity and specificity were100.0% and 98.4% respectively. The sensitivity and specificity was highest in Diff Quik stained films examined by polarizing microscopy Bangladesh J Med Microbiol 2018; 12 (2): 10-13